건성안 환자에서 카보머 점안겔이 안구표면에 미치는 임상 효과 - 이종훈(Jong Hoon Lee); 문자영(Ja Young Moon); 윤현정(Hyeon-Jeong Yoon); 윤경철(Kyung Chul Yoon) (Daihan angwa haghoi jabji, 2024)
목적: 건성안 환자에서 카보머 점안겔의 사용이 건성안 환자의 증상, 눈물막 및 안구표면에 미치는 임상적 효과에 대하여 알아보고자하였다. 대상과 방법: 2022년 1월부터 2022년 12월까지 건성안으로 진단받고 기존 약제에 카보머 점안겔을 추가적으로 6개월 이상 사용한55명의 환자를 대상으로 후향적으로 분석하였다. DEQ-5 점수와 눈물막파괴시간, 쉬르머검사, 각막염색점수를 카보머 점안겔 사용전, 사용 6개월 후에 각각 조사하여 비교 분석하였다. 또한 대상 환자를 쇼그렌 건성안군과 비쇼그렌 건성안군으로 분류하여 카보머점안겔의 효과를 분석하였다. 결과: 전체 건성안군에서 DEQ-5 총 점수(p=0.02), 건조감 강도(p<0.01), 건조감 빈도(p<0.01), 눈물막파괴시간(p<0.01)에서 호전을보였다. 이 중 비쇼그렌 건성안군에서는 DEQ-5 총 점수, 건조감 강도, 눈물막파괴시간에서 유의한 호전을 보였다. 쇼그렌 건성안군에서는 DEQ-5 총 점수, 건조감 빈도, 건조감 강도, 눈물막파괴시간에서 유의한 호전을 보였다. 비쇼그렌 건성안 및 쇼그렌 건성안군모두에서 눈물막파괴시간이 짧은 군이 DEQ-5 총 점수의 유의한 호전을 보였다. 결론: 6개월 이상의 추가적인 카보머 점안겔 사용은 건성안 증상과 눈물막파괴시간을 개선시켰으며 특히 눈물막파괴시간이 짧은 건성안 환자에서 건성안 증상을 경감시키는 효과적인 치료 방법이 될 수 있다. Purpose: We investigated the clinical effects of Siccafluid carbomer eye gel on the symptoms, tear film, and ocular surface in dry eye patients. Methods: Fifty-five patients with dry eye syndrome were also treated with carbomer eye gel for 6 months. The Dry Eye Questionnaire (DEQ-5), tear film breakup time (TBUT), Schirmer’s test, and ocular surface staining score were assessed during follow-up. Patients were classified into Sjögren’s syndrome and non-Sjögren’s syndrome groups and the effects of the carbomer eye drops in each group were analyzed. Results: Overall, the dry eye patients showed significant improvement in the total DEQ-5 score, frequency and intensity of dryness, and TBUT 6 months after treatment. In the non-Sjögren’s group, the total DEQ-5 score, intensity of dryness, and TBUT improved, while in the Sjögren’s group, the total DEQ-5 score, frequency and intensity of dryness, and TBUT improved. In both groups, patients with a shorter TBUT showed a significant improvement in the total DEQ-5 score. Conclusions: After 6 months of carbomer eye gel use in patients with dry eye syndrome, the symptoms of ocular dryness and tear film breakup time improved. In patients with dry eye syndrome who have a short TBUT, this can be an effective treatment for alleviating dry eye symptoms. KCI Citation Count: 0